Modelling of the elementary surface processes occurring in the course of heterogeneous catalytic reactions - Holovko, M.F.; Vakarin, E.V. (Condensed Matter Physics, 2000)
A short review of theoretical results on the Langmuir-Hinschelwood and Eley-Rideal reaction schemes is presented. It is shown that the rates of elementary processes at the surface are coupled through the bulk properties of adsorbing species. This concerns the dependence of the chemical potential on the association-dissociation balance and on the adsorbate density near the surface. Adsorption is shown to be sensitive to a mechanism of dimer adsorption (associative or dissociative). Dissociative adsorption gives a nonmonotonic behaviour of the coverage with the surface activity. Simultaneously, the dissociation degree increases with increasing adsorption. The associative adsorption implies the existence of a low-density critical point around which the adsorption isotherms are discontinuous. This causes an abnormal low surface diffusion at low densities. Implementation of these results to kinetic properties are brieﬂy discussed.